Influência do pH e da temperatura de precipitação nas características estruturais dos hidróxidos de alumínio preparados a partir de soluções aquosas de nitrato - Vollet, Dimas Roberto [UNESP]; Donatti, Dario Antonio [UNESP]; Domingos, Roberto Naves [UNESP]; Camargo Jr., Hélio (My University, 1996)
Aluminium Hydroxides were precipitated from Aluminium Nitrate and Ammonium Hydroxide, at the temperatures 64°C (hot) and 25°C (cold), under the pH conditions 5, 7 and 9. The samples were characterized by X-Ray Diffraction (XRD) and Differential Thermal Analysis (DTA). The hydroxide precipitated at pH 9 and 64°C is built up by pseudoboehmite and a minor share of others apparently amorphous hydroxides. The crystallinity of the hot yielded pseudoboehmite diminishes with the pH. The crystallite size was evaluated as about 40Å for the best crystallized sample. The cold precipitated product is apparently composed by amorphous or very poorly crystallized hydroxides. Upon heating, the cold precipitated hydroxides, and the low pH and hot precipitated hydroxide, release their structural water before the occurrence, about 430°C, of the transition of the pseudoboehmite to γ-alumina, and exhibit a shifting (towards low temperature side) and a broadening in the peak of the transition to α-alumina, which occurs at 1200°C in the pseudoboehmite pattern. The yielded pseudoboehmite peptized by HNO3 addition and gelified by evaporation in a critical concentration approximately 0.17gcm-3.
Influence of pH and precipitation temperature on the structural characteristics of aluminium hydroxides prepared form nitrate aqueous solutions
Keywords: Alumina; Boehmite; Peptization; Sol-gel